Heritability for resistance to Puccinia psidii Winter rust in Eucalyptus grandis Hill ex Maiden in Southwestern Brazil - Miranda, Aline Cristina [UNESP]; Moraes, Mario Luiz Teixeira de [UNESP]; Tambarussi, Evandro Vagner; Furtado, Edson Luiz [UNESP]; Mori, Edson Seizo [UNESP]; Silva, Paulo Roberto Arbex [UNESP]; Sebbenn, Alexandre Magno [UNESP] (Springer Nature, 2013)
The climates of the central and southern regions of São Paulo state in Brazil favor pathogens such as Puccinia psidii Winter, which causes a common and severe disease in Eucalyptus plantations under 2 years old. We studied genetic parameters including genotype by environment interaction (G × E) of resistance to P. psidii rust in Eucalyptus grandis at nine sites in São Paulo State. Open-pollinated progeny from ten 'provenances' were established in a randomized complete block design; at individual sites there were from 134 to 160 progenies, from four to eight blocks, and five to six trees per plot. Significant provenance and progeny(provenance) differences were detected, as was G × E involving progeny(provenance). However, the G × E involved little if any rank changes, indicating that selection can be done efficiently at a single site, if the disease level is sufficient. The estimated coefficient of genetic variation among the progeny within provenances CVg was high and variable among the sites (ranging from 11 % to 36. 7 %), demonstrating different expression of genetic variability among the sites. The estimated heritability at the individual-tree level h2 and within a plot hw 2 ranged from low to intermediate (ranging from 0. 04 to 0. 46) and was high at the progeny-mean level hf 2 (ranging from 0. 30 to 0. 86). Our study shows good prospects of controlling this disease by selection among and within progenies in a single site. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Disease resistance; Eucalyptus grandis; Genetic parameters; Puccinia psidii; Tree breeding; Eucalyptus